Growth and Progression of TRAMP Prostate Tumors in Relationship to Diet and Obesity - Melissa J. L. Bonorden; Michael E. Grossmann; Sarah A. Ewing; Olga P. Rogozina; Amitabha Ray; Katai J. Nkhata; D. Joshua Liao; Joseph P. Grande; Margot P. Cleary (Prostate Cancer)
To clarify effects of diet and body weight on prostate cancer development, three studies were undertaken using the TRAMP mouse model of this disease. In the first experiment, obesity was induced by injection of gold thioglucose (GTG). Age of prostate tumor detection (~33 wk) and death (~43 wk) was not significantly different among the groups. In the second study, TRAMP-C2 cells were injected into syngeneic C57BL6 mice and tumor progression was evaluated in mice fed either high-fat or low-fat diets. The high fat fed mice had larger tumors than did the low-fat fed mice. In the third study, tumor development was followed in TRAMP mice fed a high fat diet from 6 weeks of age. There were no significant effects of body weight status or diet on tumor development among the groups. When the tumors were examined for the neuroendocrine marker synaptophysin, there was no correlation with either body weight or diet. However, there was a significant correlation of the expression of synaptophysin with earlier age to tumor detection and death. In summary, TRAMP-C2 cells grew faster when the mice were fed a high-fat diet. Further synaptophysin may be a marker of poor prognosis independent of weight and diet.